The lysostaphin endopeptidase resistance gene (epr) specifies modification of peptidoglycan cross bridges in Staphylococcus simulans and Staphylococcus aureus. - DeHart, H P (1995)
Staphylococcus simulans biovar staphylolyticus produces an extracellular glycylglycine endopeptidase (lysostaphin) that lyses other staphylococci by hydrolyzing the cross bridges in their cell wall peptidoglycans. The genes for endopeptidase (end) and endopeptidase resistance (epr) reside on plasmid pACK1. An 8.4-kb fragment containing end was cloned into shuttle vector pL150 and was then introduced into Staphylococcus aureus RN4220. The recombinant S. aureus cells produced endopeptidase and were resistant to lysis by the enzyme, which indicated that the cloned fragment also contained epr. Treatments to remove accessory wall polymers (proteins, teichoic acids, and lipoteichoic acids) did not change the endopeptidase sensitivity of walls from strains of S. simulans biovar staphylolyticus or of S. aureus with and without epr. Immunological analyses of various wall fractions showed that there were epitopes associated with endopeptidase resistance and that these epitopes were found only on the peptidoglycans of epr+ strains of both species. Treatment of purified peptidoglycans with endopeptidase confirmed that resistance or susceptibility of both species was a property of the peptidoglycan itself. A comparison of the chemical compositions of these peptidoglycans revealed that cross bridges in the epr+ cells contained more serine and fewer glycine residues than those of cells without epr. The presence of the 8.4-kb fragment from pACK1 also increased the susceptibility of both species to methicillin.